LINGUOCULTUROLOGY, INTERCULTURAL COMMUNICATION AND CROSS-CULTURAL LINGUISTICS IN HIGHER EDUCATION - Tokhta Ametovna Yuldasheva (Western European Studies, 2024)
This article discusses linguistic and cultural studies that study the relationship and interaction of culture and language
Keywords: cross-cultural; intercultural; theorists